2021
DOI: 10.3390/ijms22126277
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights into the Interplay of Alpha-Synuclein and Sphingolipid Signaling in Parkinson’s Disease

Abstract: Molecular studies have provided increasing evidence that Parkinson’s disease (PD) is a protein conformational disease, where the spread of alpha-synuclein (ASN) pathology along the neuraxis correlates with clinical disease outcome. Pathogenic forms of ASN evoke oxidative stress (OS), neuroinflammation, and protein alterations in neighboring cells, thereby intensifying ASN toxicity, neurodegeneration, and neuronal death. A number of evidence suggest that homeostasis between bioactive sphingolipids with opposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 217 publications
(343 reference statements)
1
7
0
Order By: Relevance
“…Previously, decreased GCase activity was demonstrated in blood and brain samples of PD and DLB patients compared to controls [ 15 , 56 ], and at the same time, we and other researchers did not reveal a decrease in GCase activity in blood samples of PD patients [ 20 , 57 ]. Nevertheless, in the current study, increased HexSph concentration, which is a substrate of GCase, was found in late-onset SCZ patients compared to sPD patients and controls which supports the data about the role of ceramide metabolism in SCZ pathogenesis ( Figure 2 ) [ 58 ]. Our data support the role of ceramide metabolism in SCZ pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, decreased GCase activity was demonstrated in blood and brain samples of PD and DLB patients compared to controls [ 15 , 56 ], and at the same time, we and other researchers did not reveal a decrease in GCase activity in blood samples of PD patients [ 20 , 57 ]. Nevertheless, in the current study, increased HexSph concentration, which is a substrate of GCase, was found in late-onset SCZ patients compared to sPD patients and controls which supports the data about the role of ceramide metabolism in SCZ pathogenesis ( Figure 2 ) [ 58 ]. Our data support the role of ceramide metabolism in SCZ pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…The secreted BDNF enables to mediate multiple processes in the mammalian brain including sleep deprivation, memory, mode disorder, neuronal differentiation and growth, synapse formation, and plasticity [11,[37][38][39]. Due to the multiple physiological functions of BDNF in the healthcare industry such as Parkinson's disease [40,41], the growing supply-demand gap will be a great challenge for the scientists to fill in and the PMPs will be the batter option. For the plant-based expression system, chloroplast transformation has emerged as a new alternative to generate transplastomic plants due to some attractive features over nuclear transformation.…”
Section: Discussionmentioning
confidence: 99%
“…But this simplification to create “pure” models may then undermine how preclinical models accurately represent their respective human condition. For example, cross-seeding in multiple proteinopathies is a recognized phenomenon in parkinsonian disorders ( Williams et al, 2020 ) and the interplay with other pathologies outside of proteinopathies is also known ( Motyl et al, 2021 ).…”
Section: From Preclinical Success To Clinical Disappointment: Possibl...mentioning
confidence: 99%